Peacebuilding and international administration : the cases of Bosnia and Herzegovina and Kosovo - Van Willigen, Niels. (Routledge advances in international relations and global politics, 2013)
"This book provides a detailed historical and political analysis of the role and effectiveness of international administration in state-building. It analyses how the international administrations in Bosnia and Herzegovina and Kosovo have attempted to create sustainable political institutions and to what extent they have been successful in doing so"--